Minat Mahasiswa Pendidikan Teknik Bangunan Terhadap Jasa Konstruksi Teknik Sipil - Renata Shinta G Simamora; Amos Neolaka; Dadang Suyadi (Jurnal Pensil)
The objective of this study to find out the percentage of Interest of Educational civil engineering with engineering construction services. The study was conducted in May-July 2012. The methods used to determine the percentage of student interest in construction services is a descriptive study with survey methods or qualitative approach method then it doesn't test the hypothesis.